A replication study of the credit card effect on spending behavior and an extension to mobile payments. (May 2021) - Liu, Yunxin; Dewitte, Siegfried
Abstract: Prior research has shown that credit cards increase spending behavior as measured by the willingness to pay (WTP) or basket value. This research aims to replicate the credit card effect and to extend this effect to mobile payments. In four empirical studies, of which three online studies and one lab study (total n = 692), we manipulated payment methods (i.e., cash, credit cards, and mobile payments) and measured spending behavior (i.e., WTP and basket value). Across four studies, we did not replicate the credit card effect on either measure of spending behavior, suggesting the effect in the literature may be inflated or may have been fading away. A meta-analysis of the relevant literature revealed the expected credit card effect but also showed that the credit card effect has become weaker through the years and that this effect is contingent on the location of data collection. We also did not find evidence that the credit card effect extends to mobile payments on either measure of spending behavior in the three online studies. However, we found a significant difference between mobile payments and cash on the basket value measure (but not for the WTP measure) in the lab study. This paper also explored whether the pain of payment or payment convenience may be a mechanism underlying the relationship between payment methods and spending behavior. Although the pain of payment tended to be lower and the payment convenience tended to be higher for mobile payments, these effects did not translate into more spending behaviors. Highlights: Prior research has shown that credit cards increase spending behavior as measured by the WTP or basket value. We study how mobile payments (and credit cards) versus cash affect the WTP and basket value. The credit card effect has become weaker over the years. The credit card effect cannot be extended to mobile payments in most cases.